Reaction engineering for protein modification: tools for chemistry and biology - Chalker, J (2011)
Chemical modification of proteins is critical for many areas of biochemistry and medicine. Several methods for site-selective protein modification are reported in this Thesis that are useful in accessing both natural and artificial protein architectures. Multiple, complementary methods for the conversion of cysteine to dehydroalanine are described. Dehydroalanine is used as a general precursor to several post-translational modifications and glycosylation, polyprenylation, phosphorylation, and lysine methylation and acetylation are all accessible. These modifications and their mimics were explored on multiple proteins, including histone proteins. Unnatural modifications were also explored. The first examples of olefin metathesis and Suzuki-Miyaura cross-coupling on protein substrates are reported. Allyl sulfides were discovered to be remarkably reactive substrates in olefin metathesis, allowing use of this reaction in water and on proteins. For Suzuki-Miyaura cross-coupling, a new catalyst is described that is fully compatible with proteins. Both olefin metathesis and cross-coupling allow the formation of carbon-carbon bonds on proteins. The prospects of these transformations in chemical biology are discussed. Finally, a novel strategy is reported for the installation of natural, unnatural, and post-translationally modified amino acid residues on proteins. This technology relies on addition of carbon radicals to dehydroalanine. This method of "chemical mutagenesis" is anticipated to complement standard genetic manipulation of protein structure.